SOUND, TECHNOLOGY, AND HEALING: EXPLORING MUSIC THERAPY IN HEALTHCARE - Wankhade, Nisha; Garud, Sharmishtha K; Naikwadi , Kiran Bibhishan; E. Rajesh; Kariveliparambil, Ashifa; Karwande, Vijay Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The growing popularity of music therapy as a complementary treatment option in the contemporary healthcare system is associated with the capacity of this method to promote emotional, psychological, and physiological health. By combining the sound-based therapeutic practice with the new digital technology, the application has opened new possibilities of making the music therapy interventions more effective and more accessible. This paper analyzes the interface of sound, technology, and healing through the aspects of music therapy within the medical facility context and the possibilities of technology-based systems of therapeutic assistants. The paper involves itself in the history and theories of music therapy, and highlights the psychological and neurological processes involved in the human health in the sound process. An in-depth survey of the literature available points at the clinical usability of music therapy in mental health care, neurological rehabilitation, pain control, and patient care. The study is also exploring the potential of the emerging technologies, such as digital audio processing, wearable health sensors, artificial intelligence, mobile health applications, and immersive virtual environments, in assisting personalized music therapy intervention. The technologies allow creating adaptive therapeutic systems that react on patient physiological indications and emotional conditions in real-time. On the basis of this analysis, the paper will present a technology-based model of music therapy aimed at incorporating patient monitoring, generating therapeutic music, interactive feedback systems, and connecting with healthcare systems. The framework that is offered to be implemented will contribute to better patient interactions, increased therapy customization, and the possibility to evaluate the effectiveness of therapy using the data. In addition, the paper addresses the measures of evaluation of clinical ecoefficiency, usability, and ethical evaluation of technology-based music therapeutic systems. Some obstacles facing the therapeutic music design process like technological awareness, cultural sensitivity, therapeutic music design protocols, and standardization of therapeutic protocols are also discussed. The results indicate that the combination of modern technologies and music therapy procedures can greatly increase the opportunities of sound-based medicine in healthcare. The future of research is in creation of AI-controlled individualized music therapy systems, immersive therapeutic spaces, and standardized clinical models that will enable the further integration of music therapy into the modern healthcare systems.